A prospective study of maternal, fetal and neonatal deaths in low- and middle-income countries - Sarah Saleem; Elizabeth M McClure; Shivaprasad S Goudar; Archana Patel; Fabian Esamai; Ana Garces; Elwyn Chomba; Fernando Althabe; Janet Moore; Bhalachandra Kodkany; Omrana Pasha; Jose Belizan; et al. (The World Health Organization, 2014)
Objective To quantify maternal, fetal and neonatal mortality in low- and middle-income countries, to identify when deaths occur and to identify relationships between maternal deaths and stillbirths and neonatal deaths. Methods A prospective study of pregnancy outcomes was performed in 106 communities at seven sites in Argentina, Guatemala, India, Kenya, Pakistan and Zambia. Pregnant women were enrolled and followed until six weeks postpartum. Findings Between 2010 and 2012, 214 070 of 220 235 enrolled women (97.2%) completed follow-up. The maternal mortality ratio was 168 per 100 000 live births, ranging from 69 per 100 000 in Argentina to 316 per 100 000 in Pakistan. Overall, 29% (98/336) of maternal deaths occurred around the time of delivery: most were attributed to haemorrhage (86/336), pre-eclampsia or eclampsia (55/336) or sepsis (39/336). Around 70% (4349/6213) of stillbirths were probably intrapartum; 34% (1804/5230) of neonates died on the day of delivery and 14% (755/5230) died the day after. Stillbirths were more common in women who died than in those alive six weeks postpartum (risk ratio, RR: 9.48; 95% confidence interval, CI: 7.97-11.27), as were perinatal deaths (RR: 4.30; 95% CI: 3.26-5.67) and 7-day (RR: 3.94; 95% CI: 2.74-5.65) and 28-day neonatal deaths (RR: 7.36; 95% CI: 5.54-9.77). Conclusion Most maternal, fetal and neonatal deaths occurred at or around delivery and were attributed to preventable causes. Maternal death increased the risk of perinatal and neonatal death. Improving obstetric and neonatal care around the time of birth offers the greatest chance of reducing mortality.